Christ's Integrity as a Bridge for Value Gaps: a Dialogue Between Paul David Tripp's Theology and 1 Peter 2:21–23 - Yoelianna Herawaty Onggy; Dennis Lesmana; Antakirana Antakirana (MAHABBAH: Journal of Religion and Education, 2026)
The crisis of integrity in Christian leadership often manifests itself in the gap between confessed faith and the values that functionally govern life and leadership practices. Paul David Tripp calls this phenomenon the value gap, which is the gap between confessional values and functional values that causes the gospel to no longer function as the operational center of life. This study aims to integrate Tripp's theological diagnosis with grammatical-historical exegesis of 1 Peter 2:21–23 in order to formulate the integrity of Christ as the theological foundation that bridges this value gap. Using a qualitative approach with biblical-analytical theological methods through conceptual analysis of Tripp's thought, exegesis of the text of 1 Peter 2:21 23, and theological-constructive synthesis. The results of the study show that the integrity of Christ is constructed as a whole structure of life in the context of suffering, which includes a normative lifestyle, relational honesty without manipulation, and sustained theological surrender to God. This research contributes to the theological discourse of Christian leadership by presenting the integrity of Christ as a theological bridge that restores the gospel as the center of life and leadership, so that the gap between the faith recognized and the practice of living can be bridged structurally, not just normatively.